Using the six minute walk test to evaluate walking capacity in patients with stroke - Daniel, Christiane Riedi; Battistella, Linamara Rizzo (Acta Fisiátrica, 2014)
The 6-minute walk test (6MWT) measures the maximum distance that a person can walk in 6 minutes. The test is gaining popularity because it assesses the functional capacity of different patients and is considered a simple, safe, valid, inexpensive, and noninvasive cardiopulmonary test. Objective: The aim of this review was to investigate the applicability of the six-minute walk test in stroke survivors. Method: A literature search of MedLine (PubMed) databases dating from January 1, 2000 to April 16, 2013 was performed. The search terms used were stroke (or cerebrovascular accident or hemiplegia) and walking (mobility limitation). Author number one reviewed the titles and/or abstracts of displayed articles and determined their relevance to this review. Full text copies of relevant articles were obtained. Reference lists were screened for identification of other relevant articles. Only articles written in English were included in this review. Results: The 31 included studies were divided into 9 randomized controlled trials, 2 case-control studies, 5 prospective studies, and 15 cross-sectional studies and involved 1,824 surviving stroke patients, 146 healthy controls, and 38 Multiple Sclerosis patients. Conclusion: The 6MWT is useful in evaluating de functional capacity of patients with stroke, however, it should be used along with other assessment tools to determine the general profile of these patients. More studies are necessary to verify the factors that influence the test results and as a way to supplement them.